BUSINESS COMMUNICATION AND GLOBALIZED ENGLISH: RECENT DEFINITIONS AND APPLICATIONS OF A CONCEPT ACROSS THE CORPORATE WORLD - Dra. Fee-Alexandra HAASE (Fonseca, Journal of Communication, 2023)
This article approaches ‘business communication’ as a multi-layered economic phenomenon of the corporate society of the globalized business world. In academic education systems and in the business world under the term ‘business communication’ various definitions exist, which are applied across the fields of academic studies and in the business world. After the comparison of definitions of ‘business communication’, we demonstrate the various layers of business communication in the contemporary corporate world based upon a model of the corporate world and these cases using examples of companies implementing ‘business communication’ into their corporate structure.